2022
DOI: 10.3390/plants11060812
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Freezing Stress in Peach Based on Multi-Omics and Biotechnology: An Overview

Abstract: In nature or field conditions, plants are frequently exposed to diverse environmental stressors. Among abiotic stresses, the low temperature of freezing conditions is a critical factor that influences plants, including horticultural crops, decreasing their growth, development, and eventually quality and productivity. Fortunately, plants have developed a mechanism to improve the tolerance to freezing during exposure to a range of low temperatures. In this present review, current findings on freezing stress phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 132 publications
0
10
0
Order By: Relevance
“…Cold conditions, including freezing, are among the major abiotic stressors encountered by deciduous fruit trees, particularly peach ( Prunus persica ) trees. Peach is a highly prized, important seasonal fruit grown worldwide, including in South Korea ( Muthuramalingam et al., 2022 ). Over the past decade, owing to climate change and global warming, the peach blooming period has advanced by approximately 13 days ( https://data.kma.go.kr ).…”
Section: Introductionmentioning
confidence: 99%
“…Cold conditions, including freezing, are among the major abiotic stressors encountered by deciduous fruit trees, particularly peach ( Prunus persica ) trees. Peach is a highly prized, important seasonal fruit grown worldwide, including in South Korea ( Muthuramalingam et al., 2022 ). Over the past decade, owing to climate change and global warming, the peach blooming period has advanced by approximately 13 days ( https://data.kma.go.kr ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, when the temperature drops below 10–12 ℃, young plants begin to show cold stress symptoms on their leaves [ 3 , 4 ]. Several studies have shown that cold can directly affect photosynthetic potential and energy production, chlorophyll content, carotenoid content, increase in reactive oxygen species (ROS), while amino acid content is significantly reduced [ 5 7 ]. In addition to these biochemical attributes, transcriptome level studies have shown that cold tolerant genotypes exhibit higher gene expression for phytohormone-related genes, including jasmonic acid (JA), brassinosteroids (BRs) and others, MAPK signaling, and secondary metabolite biosynthesis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cold-induced photoinhibition can affect fruit development [ 9 ]. Mango fruits exhibit pitting, rooting, darkening of lenticel, changes in fruit peel color, and pulp quality traits [ 5 ]. Cold stress can increase abortion of embryos [ 10 ] and change fruit firmness by modifying cell-wall related polymers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first peach genome was reported in 2010, omics approaches (e.g., genomics, transcriptomics, proteomics, and metabolomics) have been widely used to investigate the roles of cold tolerance associated genes in peach ( Muthuramalingam et al., 2022 ). Digital expression analyses of EST datasets identified two promoters – Ppbec1 encoding endochitinase (C2131) and Ppxero2 encoding dehydrin (C254) as cold-inducible promoters for peach and reported the heterologous regulation of these promoters in peach at low temperatures ( Tittarelli et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%